Proceedings of the Sixth International Conference on Language, Literature, Culture, and Education (ICOLLITE 2022) 2022
DOI: 10.2991/978-2-494069-91-6_14
|View full text |Cite
|
Sign up to set email alerts
|

The Application of Text-to-Speech Technology in Language Learning

Abstract: Technology has improved temporarily from time to time. There are a lot of technologies that had been developed to enhance language learning, and one of them is text-to-speech technology. Text-to-speech technology is a form of system that can convert phoneme to audio. It has provided an impact in language learning since it was developed. This article presents how the application of text-to-speech technology is used in language learning, including the negative and positive side of text-to-speech technology in la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 11 publications
0
0
0
Order By: Relevance
“…AI helps create a learning environment that follows the era's development, intensifying involvement, and showcasing flexibility in learning (Miller & Wu, 2021;UNESCO IITE, 2020). In a writing class, AI is implemented through the use of different apps, such as AI Kaku, ChatGPT, Eskritor, Grammarly, Plot Generator, Poem Generator, Speech-to-Text, Text-to-Speech, Smodin, and other apps (Fitria, 2021;Gayed et al, 2022;Kangasharju et al, 2022;Razack et al, 2021;Sumakul et al, 2022b;Widyana et al, 2022).…”
Section: Literature Review Artificial Intelligence Technology In An A...mentioning
confidence: 99%
“…AI helps create a learning environment that follows the era's development, intensifying involvement, and showcasing flexibility in learning (Miller & Wu, 2021;UNESCO IITE, 2020). In a writing class, AI is implemented through the use of different apps, such as AI Kaku, ChatGPT, Eskritor, Grammarly, Plot Generator, Poem Generator, Speech-to-Text, Text-to-Speech, Smodin, and other apps (Fitria, 2021;Gayed et al, 2022;Kangasharju et al, 2022;Razack et al, 2021;Sumakul et al, 2022b;Widyana et al, 2022).…”
Section: Literature Review Artificial Intelligence Technology In An A...mentioning
confidence: 99%
“…Including these elements in e-modules can help students improve their literacy, create stimulating learning environments, and develop their creativity and practical thinking skills (Yulando et al, 2019). Widyana et al (2022) and Istiqomah et al (2021) suggested that text-tospeech features of e-modules could be an effective tool in language learning, just like the robot icon dubbed E-Blithe, which acts as the text-to-speech image for the developed E-SelfIMo.…”
Section: Development Of E-selfimomentioning
confidence: 99%
“…Text-to-speech technology is a system capable of converting phonemes to sound. Occasionally, technology has been enhanced temporarily (Widyana, Jerusalem, and Yumechas 2022). Recently, technology has advanced quite quickly (Lin and Wu 2014).…”
Section: Introductionmentioning
confidence: 99%